Evaluasi Perancangan Antarmuka untuk Membangun User Experience pada Layanan SInTA Universitas Kristen Duta Wacana Yogyakarta - Neshia Aditya Santoso; Gloria Virginia; Budi Susanto (Jurusan Teknologi Informasi Universitas Semarang, 2017)
SInTA is a search engine developed by Duta Wacana Christian University (DWCU) to locate references of final task reports or thesis ever made by DWCU students.The existence and function of SInTA is not widely known by students. In addition, SInTA still require many improvements on feature and UI design to simplify the interaction between users and interface.This research use individual expert review approach to evaluate interface, whereas data divided into 6 User Experience measurement scales. The result of evaluation is User Experience recommendation which used to build prototype.Considering User Experience shall be created a prototype which should attract users, meet the needs of users, and satisfy the users. In this research, prototype has higher User Experience mean values rather than SInTA old interface, thereby the research be assessed as being successful.